The Effects of Thymoquinone Loaded in Alginate Scaffold on Bone Regeneration in Rabbit Mandible Defect: The Effects of Thymoquinone on Bone Regeneration: The Effects of Thymoquinone on Bone Regeneration - Aliabadi, Ehsan; Farahmand, Mohammad Mehdi; Talaei-Khozani, Tahereh; Shahsavari-pour, Sheila (Galen Medical Journal, 2023)
Background: Thymoquinone (TQ) has some beneficial roles in bone repair. Local administration of the drugs by loading them into a scaffold leads to releasing higher concentrations of a drug in the appropriate position. This study was conducted to evaluate the effects of the local administration of TQ loaded in an alginate scaffold on bone regeneration in rabbit mandibular defect. Materials and Methods: In this experimental study, male rabbits with mandible defect were divided into 3 groups that received either alginate containing 50µM TQ, alginate or remained untreated. Then each group was subdivided into 2 groups that followed for 4 and 8 weeks (n=5). The radiological opacity, histopathology, and histomorphometrical analysis were done and data were analyzed by ANOVA and Tukey. Results: Radiological examination indicated that the presence of TQ had no significant effect on the turbidity of the images (P=0.595). TQ treatment significantly increased the bone area after 4 (P=0.011, P=0.0021, respectively) and 8 weeks (8w P=0.019, P<0.001, respectively) compared to alginate-treated and control defects. TQ also elevated the number of osteocytes (4wP<0.001, P=0.001 and 8w P<0.001, P<0.001, respectively) and osteoblasts (P<0.001, P<0.001, respectively) compared to the group receiving alginate and control. However, at 8 weeks, the number of osteoblasts was statistically similar in all the groups. In this week, although the average number of osteoblasts in the defects treated with TQ was significantly higher than the control group (P=0.01), it was similar to the group that received alginate. Conclusion: It seems that alginate containing TQ has positive effects on bone healing. TQ can be suggested as a good additive to improve bone healing and accelerate bone repair.